Secular changes in growth among japanese children over 100 years (1900-2000) - Kagawa, Masaharu; Tahara, Y.; Moji, K.; Nakao, R.; Aoyagi, K.; Hills, A. (HEC Press, 2011)
Human growth is associated with complex interactions between genetic and environmental factors. While research has reported increased body size and body mass index (BMI) of Japanese children, few studies have compared the magnitude of increments in growth before and after World War II (WW II) and also considered other social and economical events that may have influenced the growth of children. The current study assessed the secular change in growth in Japanese children and adolescents aged between 6 and 17 years using data from the School Health Statistics Survey conducted between 1900 and 2000 with consideration of key social changes during the 20th Century. Over the 100-year period, Japanese boys had height and weight increments of 1.0-2.0 cm per decade and 0.4-1.7 kg per decade whereas girls had rates of 1.1-1.9 cm and 0.4-1.5 kg per decade, respectively. The rates of height increment were significantly (p < 0.05) different between pre-, during and post-WW II periods. While Japanese children were considerably larger in 2000 compared to 1900, increments between 1950 and 1960 reflected catch-up growth to restore physical size seen in children prior to WW II. The increments in body size continued after 1960 with greatest changes seen across the pubertal years. While increments in BMI were evident in most age groups, the BMI of 17-year-old girls was consistent over the 100 years. Results clarified secular changes in growth in Japanese school children across the 20th Century and possible factors contributing to these changes.